2009
DOI: 10.1177/0269881109102530
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-associated weight loss

Abstract: Clozapine is associated with weight gain. We report three patients with substantial weight loss following treatment with clozapine. The weight loss observed in the three patients was 33, 18 and 14.4 kg with percentage loss of body weight of 49, 18 and 21 respectively. Two patients had diabetes mellitus. History, physical examination and extensive investigations in the three patients did not reveal any cause that could account for the weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Regardless of these beneficial effects, many studies have consistently found that schizophrenic patients treated with antipsychotics are much more likely to show metabolic syndrome including hyperglycaemia than the general population . Although the high incidence of hyperglycaemia in schizophrenic patients treated with antipsychotics is thought to be caused by increases in body mass, the rapid induction of hyperglycaemia has also been reported in patients without a weight gain . Furthermore, the discontinuation of antipsychotic drugs leads to the restoration of normal glucose control in patients .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of these beneficial effects, many studies have consistently found that schizophrenic patients treated with antipsychotics are much more likely to show metabolic syndrome including hyperglycaemia than the general population . Although the high incidence of hyperglycaemia in schizophrenic patients treated with antipsychotics is thought to be caused by increases in body mass, the rapid induction of hyperglycaemia has also been reported in patients without a weight gain . Furthermore, the discontinuation of antipsychotic drugs leads to the restoration of normal glucose control in patients .…”
Section: Introductionmentioning
confidence: 99%
“…Another recent case series reported weight loss following treatment with clozapine in three patients, with percentage loss of body weight of 49%, 21% and 19%,11 which the authors speculate could be due to genetic variation in neuroreceptors. A further case series reported weight loss in five patients who failed to respond to clozapine treatment.…”
Section: Discussionmentioning
confidence: 92%
“…A number of previous case reports of clozapine-induced weight loss have trickled over the years. Earlier reports indicated an association between clozapine and weight loss that may be related to genetic variability in neuroreceptors 20. In 2011, Apian and colleagues noticed a 10 kg reduction in weight a year after a switch was made from olanzapine to clozapine.…”
Section: Discussionmentioning
confidence: 99%